Telemedicine in epilepsy care: doc-to-doc applications Part I: State of the art, challenges, and perspectives - Mues, Sigrid; Hamer, Hajo; Von Podewils, Felix; Sotoodeh, Ali; Rosenow, Felix; Wellmer, Joerg; Zoellner, Johann Philipp (Zeitschrift für Epileptologie, 2021)
Telemedical doc-to-doc applications in epilepsy care can help to provide the special expertise of adult or pediatric epileptologists area wide, as they make it possible to provide medical services across spatial distances. Various solutions are being developed both nationally and internationally for this purpose; however, there are organizational, technical, legal and economic challenges. The long-term perspective of the various current approaches is unclear. Ultimately, business models will have to be developed in which all players (consultation providers and requesting physician, patients, health insurers, operators of telemedical platforms and, if necessary, the respective professional associations) weigh up the specific benefits and risks.
CRIS-Team WoS Importer:2021-07-23